Respostas
respondido por:
2
Resposta: 4
Explicação passo-a-passo:
3x+3-6x+2=-x-5
3x-6x+x=-5-3
-2x=-8 (-1)
2x=8
x=8/2
x=4
respondido por:
2
Olá...
EQUAÇÃO
- QUESTÃO:
- Resolve a seguinte equação:
RESOLUÇÃO
3x + 3 - 6x + 2 = - x - 5
3x - 6x + x = - 5 - 3 - 2
-2x = - 10 >>> .(-1)
2x = 10
x = 10/2
x = 5
➖➖➖➖➖➖➖➖➖➖➖➖▶
RESPOSTA:
- x = 5
➖➖➖➖➖➖➖➖➖➖➖➖▶
- ESPERO TER AJUDADO!!!
- BONS ESTUDOS!!!
- DÚVIDAS??? COMENTE!!!
ATT: DALANA
Perguntas similares
4 anos atrás
4 anos atrás
4 anos atrás
7 anos atrás
7 anos atrás
8 anos atrás
8 anos atrás